Errors in Using Order of Adjectives in Writing Descriptive Text - Erlidawati (Medan Resource Center, 2022)
ABSTRACT writing is one of skills in learning English besides reading, writing and speaking skill. Writing is an activity write that it needs to express thought and feeling in written form. Most of students often make errors in their writing and they still do not understand in using order adjective in sentences grammatically. The objective is to increase students’ comprehension in using order adjective in writing descriptive text. The errors make by students has some reasons; firstly, they have lack of motivation from themselves, they do not interest in learning writing and the material presentation is not comfortable. Secondly, first language or mother tongue can influence the language or language interference. Thirdly, translation use in first language sentences word by word, it occurs to change of the meaning in a sentence. Therefore, to solve the students’ errors in writing descriptive text, the students have to know order adjective like; quantity, opinion, size, age, shape, color, origin, material and purpose. So, they can write sentence in a paragraph grammatically and regularly.